New functional non-dairy mixed tropical fruit juice microencapsulated by spray drying: Physicochemical characterization, bioaccessibility, genetic identification and stability. (December 2021) - Souza, Michelle; Mesquita, Amanda; Souza, Paulo; Borges, Graciele; Silva, Túlio; Converti, Attilio; Maciel, Maria Inês
Abstract: This study shows the development of a powdered non-dairy probiotic 40:60% (w/w) acerola:siriguela mixed juice. The mixed juice enriched with the probiotic Lactobacillus rhamnosus LPAA 01, Lactobacillus casei LPAA 02 and Lactobacillus plantarum LPAA 03 strains was microencapsulated by spray drying using 140 °C air inlet temperature, 0.60 L/h feed flow rate and 10% (w/w) 5 dextrose equivalent maltodextrin. Microcapsules were analyzed in terms of physicochemical characteristics, chemical composition, in vitro bioaccessibility, microbial viability and stability at 5 and 25 °C for 45 days. Viable cell counts were >6 log CFU. g −1 for up to 20 days at 5 °C and 14 days at 25 °C, and physicochemical properties of microparticles were shown to be in acceptable ranges. Each specific primer pair showed unique amplification, confirming the survival of all the three probiotics. The levels of phenolic compounds, with the exception of quercetin, as well as antioxidant activity by ORAC method increased after exposure to simulated gastrointestinal conditions. Highlights: A new non-dairy probiotic product was developed. Viable cells were >6 log CFU/g after storage for 20 days at 5 °C and 14 days at 25 °C. Multiplex PCR allowed to detect the three lactobacilli inside the microcapsules. The powdered mixed juice had high bioactive properties. Physicochemical properties were shown to be in acceptable ranges.